Improvements in the mechanical properties of the 18R↔6R high-hysteresis martensitic transformation by nanoprecipitates in CuZnAl alloys - de Castro Bubani, Franco (2012)
The 18R. ↔. 6R martensite-martensite transformation in Cu-based alloys exhibits large hysteresis, large pseudoelastic strain and weak transformation stress dependence on temperature. However, concomitant plastic deformation taking place in the 6R phase inhibits the use of these properties for applications. A novel approach to minimizing or even suppressing 6R plastic deformation during the 18R-6R transformation in CuZnAl shape-memory alloy single crystals with electronic concentration . e/. a=. 1.48 is presented. The method is based on a thermal treatment that introduces nanoprecipitates in the alloy. Results suggest that the role of CuZnAl shape-memory alloys in engineering should be reconsidered, as many energy damping applications could benefit from the huge hysteresis associated with the 18R-6R transformation, once the 6R plastic deformation is suppressed.